PENGARUH NILAI DAN GAYA HIDUP TERHADAP PREFERENSI DAN PERILAKU PEMBELIAN BUAH-BUAHAN IMPOR - Sukmaningtyas, Astari; Hartoyo, Hartoyo (Jurnal Ilmu Keluarga dan Konsumen, 2013)
This study was intended to determine the influence of values and lifestyle on the preferences and purchasing behavior of imported fruits. This study applied cross sectional design and involved 60 housewives which were randomly selected. The result showed that most of the housewives’ ethnocentrism level was categorized at low level and most of them were considered to perform family oriented lifestyle. The fruit preferences showed that imported apple and longan were more preferred than the local ones, while local oranges were more preferred than the imported one.The result also indicated that preferences toward imported longan significantly correlated with preferences toward imported apple and oranges. Regression analysis revealed that ethnocentrism significantly affect preferences of imported oranges and purchasing of imported apple. The results also confirmed that social active oriented lifestyle significantly affected purchasing of imported apple.